Transformational Nursing Leadership and Teamwork Performance: Rethinking Leadership Development in Nursing Education - Birrul Qodriyyah; Dini Tryastuti; Karyadi Karyadi (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Nursing leadership has increasingly been recognised as a decisive element in sustaining teamwork performance, patient safety, and quality of care. However, the relationship between leadership and teamwork is often discussed in a fragmented manner, with leadership treated as an individual managerial attribute and teamwork as a separate operational outcome. This article aims to critically examine how transformational nursing leadership contributes to teamwork performance and to discuss its implications for leadership development in nursing education. This study employed a structured narrative review approach by synthesising selected literature on nursing leadership, teamwork, transformational leadership, patient safety, staff retention, and leadership development. The review was organised thematically to clarify three key issues: the conceptualisation of nursing leadership in clinical practice, teamwork as a mechanism linking leadership with care quality, and transformational leadership as a developmental framework for preparing nurse leaders. The synthesis indicates that transformational leadership contributes to teamwork performance not merely by motivating individual nurses, but by shaping communication, trust, shared responsibility, mutual support, and collective accountability within clinical teams. Nevertheless, transformational leadership should not be idealised as a universal solution, since effective nursing leadership also requires operational discipline, role clarity, feedback systems, and organisational support. This article concludes that nursing education should move beyond teaching leadership as an abstract competence and instead cultivate future nurse leaders who are able to build reliable, collaborative, and patient-centred clinical teams.